Evaluation of Scatter Fraction (SF) of a 16-Ring Positron Emission Tomography (PET) System (Bangladesh Journal of Medical Physics, 2013)
Scatter fraction (SF) characteristic of a newly constructed 16-ring PET system with a FOV of 20 cm was experimentally evaluated in 2D acquisition mode (ring difference ? 3) but without septa, using a 10 cm diameter phantom. The scatter fraction measured from the backprojected images and the sinogram data aiming to find the discrepancy between the two approaches and to test the camera performance operating without septa. The images were reconstructed by the filtered backprojection (FBP) technique using some different filter functions. SF measured from the reconstructed images agreed within uncertainties and had a mean value of 26.1±0.8% at 250-850 keV energy and 12 ns coincidence time window. Scatter fraction also measured from analysis of the PET sinogram was slightly lower, at 23.6 ±0.7%. In each case, the procedure used for estimating the background under the peak is only approximate, and this may account for the slight discrepancy between the two approaches. The results so far indicate that the system can be operated in 2D mode without septa. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14691 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 81-86